Pengaruh Model Pembelajaran dan Kecerdasan Emosional terhadap Hasil Belajar Peserta Didik - Ramadhan, Puji Laila; Anwar, Muhammad; Sudding, Sudding (Program Pasca Sarjana UNM, 2020)
This study aims to determine the effect of the influence of learning models and emotional intelligence on learning outcomes of XI grade students of SMA Negeri 12 Makassar. This research method uses quasi-experimental methods used is